ISOLASI DAN IDENTIFIKASI BAHAN AKTIF PENYEBAB PEMANCARAN CAHAYA PADA BAKTERI Photobacterium phosphoreum YANG DIISOLASI DARI CUMI LAUT JEPARA INDONESIA - Ratnawulan, Ratnawulan; Pringgenis, Delianis; Arif, Idam (Makara Journal of Science, 2023)
Isolation and Identification of Active Compound Cause Light Emmitting of Bacterial Photobacterium phosphoreum Isolated from the Indonesia Jepara Marine Squid. This research carried out to study the bioluminescence process of bacterial Photobacterium phosphoreum isolated from Indonesia marine squid. The method used in the present study involved isolation, purification, electrophoresis, and the absorbance and light intensity measurement. This result show that the luciferace enzyme of bacterial Photobacterium phosphoreum or called LBPP catalyzes the emission of visible light from the reaction of reduced flavin mononucleotide (FMNH2 ), molecular oxygen (O2 ), and an aldehyde (RCOH). The electrophoresis data show that LBPP comprised of two different subunits a and b with 41kD and 38 kD molecular weights. The absorb pattern showed that the bioluminescence process centered around 516 nm and are consistent with the fluorescence data. This result concluded that the excitation state formed after LBPP bind subtracts and the ground state formed after LBPP releases product and visible light.